2006
DOI: 10.1007/s00264-005-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Labrum repair combined with arthroscopic reduction of capsular volume in shoulder instability

Abstract: We performed arthroscopic treatment of traumatic anterior and anteroinferior shoulder instability combining three procedures-labrum repair, reduction of capsular volume and suture of the rotator cuff intervalwith the aim of analysing the results with regard to stability and function. Between January 1999 and December 2003, 27 patients underwent arthroscopic treatment for labrum repair with metal anchors, reduction of capsular volume through thermal capsulorrhaphy and suture of rotator cuff interval. These pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…To our best knowledge there has been no report on volume reduction effect in the clinical in vivo scenario in arthroscopic stabilization techniques apart from our technical report on arthroscopic capsular shift [22]. Such evaluation would provide proper knowledge of how the surgical techniques affect the joint biomechanics and the anatomy of the glenohumeral joint [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge there has been no report on volume reduction effect in the clinical in vivo scenario in arthroscopic stabilization techniques apart from our technical report on arthroscopic capsular shift [22]. Such evaluation would provide proper knowledge of how the surgical techniques affect the joint biomechanics and the anatomy of the glenohumeral joint [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Capsular shift is intended to decrease volume, thus constraining the joint. The potential to reduce the joint volume has been studied before on a cadaveric shoulder model [12][13][14][15][16][17][18][19][20][21], showing that open techniques allow for higher volume reduction (40-50 %) than arthroscopic techniques (30-40 %). However, a cadaveric shoulder may not reflect a life scenario of the unstable shoulder in a much younger population and different joint capacity despite the fact that various modifications of arthroscopic techniques have been published to make either capsular shift or plication.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods that have been described for the closure of the RI differed mainly in the method of suture passing. 1,3,4,6,10,11,18 Previous arthroscopic RI closures resulted in good stability and improvement in functional status, 12 and seemed to have improved the outcome of shoulder instability repair, with up to 97% stability rates at a minimum of 2 years of follow-up. 17 Rotator interval closure alone was proven effective in the treatment of patients with an exclusive (no PBL) RI defect (27.5 mm)-associated inferior and multidirectional shoulder instability.…”
Section: Discussionmentioning
confidence: 96%
“…Only few small clinical trials had demonstrated good shoulder stability after open and arthroscopic closure of the RI. 5,12,17 We performed a retrospective study to compare the results of arthroscopic anterior shoulder instability repair with and without closure of the RI.…”
mentioning
confidence: 99%
“…Several studies [3][4][5][6][7][8][9][10][11] have reported a significant correlation between labral fixation and glenohumeral translation. In contrast, Kim et al 12 reported an insignificant correlation between the extent of the labral lesion and the frequency of glenohumeral dislocation.…”
Section: Introductionmentioning
confidence: 99%